A Light in the Wilderness - Kirkpatrick, Jane 1946- (Thorndike, Maine : Center Point Large Print, 2014)
"A dramatic story of a freed slave who has lost her husband and her freedom papers and must find a way to survive in the wilderness of the Oregon Territory"--
Keywords: Freedmen -- Fiction; African American women -- Fiction; Large type books; Oregon Territory -- Fiction -- History; Christian fiction